Teachers’ Performance in Constructing Model And Content of Speaking Skill Assessment - Firawati, Yulis (IAIN Parepare, 2023)
Material as teaching material and assessment in speaking skill assessment occupies an important role. The teacher prepares teaching materials and practical assessments. The purpose of this research is to describe teachers' performance in constructing models and content of speaking skill assessment. This research was conducted in MAN 1 and MAN 2, Parepare City. The subject of the research were 4 English teachers who had been teaching English. The teachers studied from each school were young teachers and teachers who had dozens to tens of years of teaching experience. This qualitative research method was implemented using interviews and documents and it was analyzed descriptively. The results of this research revealed that teachers in constructing model and content for speaking assessment conduct in three steps: selecting speaking activity; identification of need for material; contextual realization of material.